Effects of eluted components from 4-META/MMA-TBB adhesive resin sealer on osteoblastic cell proliferation - Aya Kawasaki; Yoshihiko Hayashi; Kajiro Yanagiguchi; Shizuka Yamada; Minoru Syudo; Kazunari Igawa; Takeshi Ikeda; Shisei Kubo; Mamoru Fujiwara (Elsevier, 2012)
Background/purpose: Adhesive resin sealer systems are applied to seal root-canal systems more effectively through the formation of a resin impregnation layer. The purpose of this study was to investigate the effects of eluted components of the adhesive, Super-Bond sealer (SBS), on the proliferation of osteoblastic cells in vitro. Materials and methods: The standard powder:liquid ratio according to the manufacturer's instructions was used to produce a cylindrical block of SBS (5 mm in diameter, 10 mm long) for this elution study. The resin block was placed on a 100-mm culture dish. Osteoblastic cells were seeded at a density of 4×106 in α-minimum essential medium containing 10% fetal bovine serum and cultured in a humidified incubator. After 3 days of culture with or without SBS, cells were retrieved and lysed according to the manufacturer's instructions. The cellular events induced by the eluted components from SBS were analyzed using an antibody assay for mitogen-activated protein kinases (MAPKs) and a 3-(4,5-dimethylthyazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Furthermore, the concentration of boron, a component of the catalyst, tri-n-butyl borane (TBB), was analyzed using inductively coupled plasma optical emission spectrometry. Results: Expression of MAPKs increased after SBS application. The MTT assay indicated that TBB, one of the components of SBS, accelerated the proliferation of osteoblastic cells. Values of boron were 1.66±0.37 and 1.74±0.30 ppm in cells cultured with and without FBS, respectively. Conclusions: The eluted components from SBS can increase the expression of some MAPKs related to osteoblastic cell proliferation and differentiation in vitro. Both the elution experiment and treatment of cell culture with SBS components indicated that the boron originating from TBB is likely to be responsible for activation of the proliferation of osteoblastic cells.